Hubungan skeptisme profesional auditor, situasi audit, etika, pengalaman audit, pengetahuan mendeteksi kekeliruan dengan pertimbangan tingkat materialitas ( pada kantor akuntan publik se-sumatera) - Erminta Riris Marito; Rita Anugerah; Rahmiati Idrus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study examined the relationship of professional skepticism audit, audit situation, ethics, audit experience, and knowledge to detect errors in consideration of the level of materiality. The study employs a field experiment involving auditors who worked on the Public Accounting Firm (KAP) and listed on the Directory Indonesian Institute of Certified Public Accountants (IAPI) 2013 Se-Sumatra. Data were obtained through questionnaires and based on pre-defined criteria there are 80 questionnaires can be used. Methods of data analysis in this study is the multiple linear regression with SPSS version 17.0. Results of regression testing (ttest) showed that the auditor's professional skepticism, audit situation, and ethical considerations have a significant relationship with the level of materiality while auditing experience and knowledge to detect mistakes not have a significant relationship with the level of materiality considerations on Public Accounting Firm (KAP) Se -Sumatra. The amount of R Square (R2) of 0.454 gives the sense that the rate of 45.40% materiality considerations professional skepticism can be explained by the audit, the audit situation, ethics, audit experience and knowledge to detect errors while 54.60% can be explained by other variables.Keywords : Consideration of the level of materiality, audit professional skepticism, audit situation, ethics, audit experience and knowledge to detect errors.